2018
DOI: 10.1007/s10695-018-0488-y
|View full text |Cite
|
Sign up to set email alerts
|

Intrafollicular thyroid hormone staining in whole-mount zebrafish (Danio rerio) embryos for the detection of thyroid hormone synthesis disruption

Abstract: Endocrine-disrupting chemicals are known to impact multiple hormonal axes of vertebrates, among which the thyroid system is crucial for multiple developmental and physiological processes. Thus, the present study focused on the semi-quantitative visualization of intrafollicular triiodothyronine (T3) and thyroxin (T4) in zebrafish embryos as a potential test system for the detection of disrupted thyroid hormone synthesis. To this end, an antibody-based fluorescence double-staining protocol for whole-mount zebraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…At ~72 hpf, endogenous TH synthesis begins (Porazzi et al, 2009;Darras et al, 2011;Gothie et al, 2019;Vancamp et al, 2019) causing internal TH levels to increase significantly, peaking at 10 dpf (T3) and 21 dpf (T4) (Chang et al, 2012). A more recent study measuring T3 and T4 levels using fluorescent antibodies found hormone levels peak earlier, at 6 dpf, and then decrease (Rehberger et al, 2018). Prior to hatching, thyroglobulin expression begins at 32 hpf and Na + /I + symporter expression starts at 40 hpf (Alt et al, 2006).…”
Section: Thyroid Hormone Localization Signaling Receptor Typesmentioning
confidence: 99%
“…At ~72 hpf, endogenous TH synthesis begins (Porazzi et al, 2009;Darras et al, 2011;Gothie et al, 2019;Vancamp et al, 2019) causing internal TH levels to increase significantly, peaking at 10 dpf (T3) and 21 dpf (T4) (Chang et al, 2012). A more recent study measuring T3 and T4 levels using fluorescent antibodies found hormone levels peak earlier, at 6 dpf, and then decrease (Rehberger et al, 2018). Prior to hatching, thyroglobulin expression begins at 32 hpf and Na + /I + symporter expression starts at 40 hpf (Alt et al, 2006).…”
Section: Thyroid Hormone Localization Signaling Receptor Typesmentioning
confidence: 99%
“…Inhibition of TPO is usually measured in in vitro assays using mammalian source materials (Friedman et al, 2016). Nevertheless, a number of studies have directly quantified T4 present in the thyroid follicles to show that model TPO inhibitors such as the pharmaceuticals PTU and methimazole (a model TPO inhibitor) reduce TH synthesis in zebrafish (Raldúa & Babin, 2009;Rehberger et al, 2018;Thienpont et al, 2011). Studies in rats (Cooper et al, 1983(Cooper et al, , 1984 and African clawed frog (Tietge et al, 2010) further support the presence of this relationship across vertebrates.…”
Section: Empirical Evidence Of Kersmentioning
confidence: 99%
“…In fish early life stages, whole-body TH level measurements are often used as a proxy for serum TH levels, because obtaining serum is practically not feasible. Time-, dose-, and incidence-concordance can be derived from the combined studies of Rehberger et al (2018) and Thienpont et al (2011) showing reduced TH synthesis after treatment with PTU and methimazole, as well as Stinckens et al (2020), If Yes, levels of confidence have been taken from the previously reviewed AOP 159.…”
Section: Empirical Evidence Of Kersmentioning
confidence: 99%
“…In addition, endpoints included in a General Developmental Score (GDS) have been associated with developmental toxicity caused by thyroid disruptors, including abnormal iridophore pigmentation, beat and glide swimming and resorption of the yolk sac (Jomaa et al, 2014). Finally, given the aforementioned conservation of thyroid development in teleosts, early detection of thyroid disruption is possible using whole-mount intrafollicular TH staining which could potentially be implemented into current OECD zebrafish assays (Rehberger et al, 2018). Interestingly, a novel fluorescent transgenic line expression under the control of the zebrafish thyroglobulin promoter allows for in vivo monitoring of thyroid gland development.…”
Section: Endpoints In Fish Models For Identification Of Thyroid Disrumentioning
confidence: 99%